2019
DOI: 10.1177/0021998319874849
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Al5083 surface hybrid nanocomposite reinforced by CNTs and Al2O3 nanoparticles using friction stir processing

Abstract: In the present study, friction stir processing was adopted for surface treatment of Al5083 by incorporation of CNT and Al2O3 nanoparticles. Microstructural, mechanical and tribological properties of the surface of Al5083/CNT, Al5083/Al2O3 and hybrid Al5083/CNT/Al2O3 nanocomposite were investigated and compared. The friction stir processing yielded a nearly uniform dispersion of CNTs and Al2O3 nanoparticles, irrespective of nanoparticle reinforcements and their weight fraction. Microstructural observations reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…As a result of the unique characteristics of nanocomposite materials, this method has been utilized to fabricate nanocomposite structures for diverse purposes. During dynamic recrystallization of grains, nanocomposite structures contain reinforcement nanoparticles that disperse along grain boundaries [4][5][6][7][8][9][10]. Al 2 O 3 , SiC, Ti 2 B, and CNT were used as reinforcement particles to strengthen the aluminum alloy matrix; hence, multiple FSP passes are carried out during the process [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of the unique characteristics of nanocomposite materials, this method has been utilized to fabricate nanocomposite structures for diverse purposes. During dynamic recrystallization of grains, nanocomposite structures contain reinforcement nanoparticles that disperse along grain boundaries [4][5][6][7][8][9][10]. Al 2 O 3 , SiC, Ti 2 B, and CNT were used as reinforcement particles to strengthen the aluminum alloy matrix; hence, multiple FSP passes are carried out during the process [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, thermal expansion response of MWCNT reinforced Al composite was studied by Zhou et al 30 and found Aluminium carbide (Al 4 C 3 ) nanostructure formation during heat treatment process led to increase load transfer capability at the interface and increase yield strength of composite. Farhad et al 31 examined Al5083 hybrid nanocomposite reinforced with CNTs and Al 2 O 3 via friction stir process and obtained additional hybridization of CNT/Al 2 O 3 collectively improved the strength and hardness. Moreover, the wear properties like wear resistance also enhanced by making hybrid composites.…”
Section: Introductionmentioning
confidence: 99%
“…The FSP process is considered one of the most effective methods for fabricating metal matrix composite surfaces because of its ability to introduce various reinforcing nanoparticles into the metal base without significant obstacles during the fabrication process [9,10]. The FSP method has been used to improve and modify the surface properties of processed aluminum alloys by using reinforced particles and ceramic materials such as Al 2 O 3 , B 4 C, SiC, VC, CWNTs, TiB 2 and others [11][12][13][14][15][16][17][18]. The hybrid composites exhibit excellent strength properties, uniformity and significantly improved microstructural behavior.…”
Section: Introductionmentioning
confidence: 99%